2010
DOI: 10.1186/1471-2407-10-682
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of PMP22 is an independent prognostic factor for disease-free and overall survival in breast cancer patients

Abstract: BackgroundGene expression of peripheral myelin protein 22 (PMP22) and the epithelial membrane proteins (EMPs) was found to be differentially expressed in invasive and non-invasive breast cell lines in a previous study. We want to evaluate the prognostic impact of the expression of these genes on breast cancer.MethodsIn a retrospective multicenter study, gene expression of PMP22 and the EMPs was measured in 249 primary breast tumors by real-time PCR. Results were statistically analyzed together with clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…increased p23 expression, significantly altered the expression of several such genes (Figure 8B) suggesting p23 may act by reprogramming gene expression profiles into more aggressive phenotypes. KYNU, CTSD and PMP22 are known to be up‐regulated in advanced metastatic cancers and correlate with poor prognosis whereas LAMB1 encodes a laminin‐1 protein shown to have reduced expression in breast cancer (Minn et al., 2005; Pruitt et al., 2013; Simpson et al., 2010; Tong et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…increased p23 expression, significantly altered the expression of several such genes (Figure 8B) suggesting p23 may act by reprogramming gene expression profiles into more aggressive phenotypes. KYNU, CTSD and PMP22 are known to be up‐regulated in advanced metastatic cancers and correlate with poor prognosis whereas LAMB1 encodes a laminin‐1 protein shown to have reduced expression in breast cancer (Minn et al., 2005; Pruitt et al., 2013; Simpson et al., 2010; Tong et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PMP22 is proved to be frequently amplified in osteosarcomas and may be involved in cell cycle to aberrant regulate cell growth in osteosarcoma tumorigenesisn [8,9]. Besides, PMP22 is observed to be differentially expressed in breast cell lines and is defined as an independent prognostic factor for overall survival in patients with breast cancer [10]. Irshad et al also have confirmed that PMP22 is a molecular signature in newly diagnosed prostate cancer with independent prognostic value [11].…”
mentioning
confidence: 94%
“…Regulation of Pmp22 mRNA by G3bp1 affects the cellular proliferation in breast cancer (Winslow et al, 2013). Pmp22 gene expression is a novel independent prognostic factor for disease free survival and overall survival for breast cancer patients and including it into a model with established prognostic factors will increase the accuracy of prognosis (Tong et al, 2010).…”
mentioning
confidence: 99%